fo012425: Auto-industrie
"Zwart-witfoto van twee arbeiders die Amerikaanse motors herstellen in een Belgische fabriek. Opschrift achteraan: U.S. Motors repaired in Belgium factory. Belgian workers test the accuracy of a newly ground crankshaft for an American truck at a factory in Belgium under contract to the U.S. Army. FULL TEXT AVAILABLE AT AMSAB-ISH"